PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS E-FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPAS MATERI PERMUKAAN BUMI KELAS V SDN 4 PURWODADI KABUPATEN GROBOGAN - Riswanti, Merita Lutfiana; Prasetyaningtyas, Fitria Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to develop and test the feasibility and effectiveness of E-flipbook learning media to improve student learning outcomes in the natural and social science, Earth's Surface material, fifth grade of state elementary school 4 Purwodadi. The method used in this study is the ADDIE research method. The sample in this study used a small group trial with a total of 10 students in fifth grade A, and a large group product test with a total of 38 students in fifth grade B at public elementary school 4 Purwodadi. The results of the E-flipbook learning media validation test were carried out by material expert lecturers and media experts. The results of the media validation with an average value of 83.34% with feasible criteria while the validation of material experts with an average of 88.34% with very feasible criteria. The effectiveness of the E-Flipbook learning media can be seen from the increase in learning outcomes. The increase in learning outcomes in the pretest and posttest from the small group test was 0.47 with moderate criteria and in the results of the large group test was 0.66 with moderate criteria. So it can be concluded that the E-flipbook learning media is feasible and effective in improving student learning outcomes.